Manifestations of symbolic violence against women in the novels of Lutfia Al-Dulaimi (Journal of the College of Basic Education, 2023)
Violence is present in all societies and in our current society in several direct and indirect forms, from physical (physical) violence in which women are threatened, beaten and killed to hidden moral (symbolic) violence, whose results are more dangerous than other types of violence because it causes psychological confusion to the victim. The research dealt with the manifestations of symbolic violence against women in the novels of Lutfia Al-Dulaimi, which tried through its narrative texts to combat violence against women in its various patterns and forms, and to create awareness of its danger, and the need to avoid it in daily life, and here the writer reflects the violent social reality with all the creative elements created by the novelist imagination, to shed light on the realistic violent behaviors practiced against women.